Interdisciplinary education and libertating education: two matters, one objective (Research, Society and Development, 2020)
It is possible to understand interdisciplinary teaching as an aspect of the same context where liberating education is placed on. As a matter of fact, educational movements call for a new methodological system of knowledge construction, which must no longer be fragmented. Indeed, the ideal is to look forward to understanding education in a broader aspect, linked to students' daily life. As a branch of this educational reality, interdisciplinarity meets this need. Still, the shown scenario allows to seek after characterizing the part of interdisciplinarity within the spectrum of liberating education. Through the idea of how important natural science is in order to acquire a rich and complete knowledge building. Along with the main subject, this essay's based on the methodology of bibliographic research. As a way to conclude that interdisciplinarity is of real importance, and applicable, several authors and studies where checked on. Despite the difficulties involving understanding and usage of the concepts. While living in a time of transformation, from traditional education to liberating education, interdisciplinarity is an essential part of this complex process.